2021
DOI: 10.1101/2021.04.26.441141
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stress granules are shock absorbers that prevent excessive innate immune responses to dsRNA

Abstract: Proper defense against microbial infection depends on the controlled activation of the immune system. This is particularly important for the innate immune receptors that recognize viral double-stranded RNA (dsRNA) and initiate antiviral immune responses with the potential of triggering systemic inflammation and immunopathology. How the functions of the dsRNA receptors and their downstream effector molecules are coordinately regulated to avoid excessive immune response is poorly understood. We here demonstrate … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 82 publications
0
20
2
Order By: Relevance
“…SGs can physically contact different membrane-bound organelles, including lysosomes or the ER, and starvation-induced SGs contact with mitochondria in human cells (Amen and Kaganovich, 2021; Lee et al, 2020; Liao et al, 2019). Furthermore, numerous mitochondrial proteins have been associated with SGs (Amen and Kaganovich, 2021; Aoyama-Ishiwatari et al, 2021; Paget et al, 2023). Our study identifies SGs as novel signalling components associated with the mammalian UPRmt and SG dynamics as a key for maintaining mitochondrial function during mitochondrial stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SGs can physically contact different membrane-bound organelles, including lysosomes or the ER, and starvation-induced SGs contact with mitochondria in human cells (Amen and Kaganovich, 2021; Lee et al, 2020; Liao et al, 2019). Furthermore, numerous mitochondrial proteins have been associated with SGs (Amen and Kaganovich, 2021; Aoyama-Ishiwatari et al, 2021; Paget et al, 2023). Our study identifies SGs as novel signalling components associated with the mammalian UPRmt and SG dynamics as a key for maintaining mitochondrial function during mitochondrial stress.…”
Section: Discussionmentioning
confidence: 99%
“…Questions remain as to the functional link between inhibition of SG assembly and mitochondrial homeostasis following UPRmt activation. Several studies support a protective role for SGs, through impairing pro-apoptotic JNK signalling (Arimoto et al, 2008; Kitajima et al, 2023), sequestration of caspases (Fujikawa et al, 2023) or suppressing production of ROS (Park and Shin, 2023; Takahashi et al, 2013) and they have been described as “shock absorbers” dampening excessive innate immune response to viral infection (Paget et al, 2023). In contrast, persistent SGs are implicated in pro-death functions during chronic stress conditions as well as neurodegenerative diseases or tumour chemotherapy (Reineke et al, 2018; Reineke and Neilson, 2019; Schwed-Gross et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…While this question will need to be explored in future studies, we surmise that autophagy degrades ERE RNAs instead of degrading their translational product. Indeed, autophagy has been reported to target viral (66) and ERE (34) dsRNA to autophagosomes. Notably, this would explain why CTA MAPs (which do not result from dsRNA) were successfully presented at higher levels after AZA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, we also observed that many GO terms related to protein degradation/catabolism and autophagy were significantly downregulated in these patients. Since ERE RNAs can trigger autophagy (34) and be degraded by the autophagic process (35), we hypothesized that enhanced autophagy in low-ERE expressing blasts could protect them from the deleterious effects that EREs have on their proliferation. This idea was explored in-depth in our next series of experiments.…”
Section: Aza-induced Eres Correlate With Innate Immune Responses In P...mentioning
confidence: 99%
See 1 more Smart Citation